Quaternized modified GA-PVA / PEI-Cl nanofiber as well as preparation method and application thereof

By quaternary amination of modified GA-PVA/PEI-Cl nanofibers, the problems of low efficiency and poor selectivity of traditional gold recycling technology are solved, and efficient selective adsorption of AuCl4- in wastewater is achieved, with broad application prospects.

CN119531125AActive Publication Date: 2025-02-28YUNNAN HONGSHENG PLATINUM IND NEW MATERIAL TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411816412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-28
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Traditional gold recycling technology has problems of low adsorbent efficiency and poor selectivity, making it difficult to effectively recover gold resources in wastewater.

Method used

Quadratic amination modified GA-PVA/PEI-Cl nanofibers were used as adsorption materials, and nanofibers were prepared by electrospinning technology, and quaternary modification of glutaraldehyde and chloro-n-propane were improved to improve the adsorption capacity of nanofibers.

Benefits of technology

The selective enrichment adsorption of AuCl4- in aqueous solution is achieved, with high adsorption capacity and good adsorption effect, and can effectively recover gold resources in wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531125A_ABST
    Figure CN119531125A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nanofibers, in particular to quaternization modified GA-PVA / PEI-Cl nanofibers and a preparation method and application thereof.The preparation method specifically comprises the following steps that S1, PVA / PEI composite nanofibers are prepared, specifically, polyvinyl alcohol powder and water are stirred for 4 h in an oil bath pan at the temperature of 85 DEG C through a magnetic stirrer, and then a uniform and transparent spinning solution, namely, a solution A, is obtained; stirring polyethyleneimine and water at room temperature for 4 hours to obtain another uniform and transparent spinning solution, namely a solution B; mixing the solution A with the solution B to obtain a solution C, and spinning the solution C in an electrostatic spinning machine to obtain PVA / PEI composite nanofibers; s2, preparing a GA-PVA / PEI nano fiber; and S3, preparing the quaternized GA-PVA / PEI-Cl nano fiber. The selective adsorption of AuCl4 <-> is realized between the prepared quaternization modified GA-PVA / PEI-Cl nanofiber and the AuCl4 <-> through the interaction of electrostatic interaction, coordination, oxidation reduction and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofibers, and in particular to quaternary ammonium modified GA-PVA / PEI-Cl nanofibers and a preparation method and application thereof. Background Art

[0002] Gold, due to its excellent corrosion resistance, low toxicity, low contact resistance and excellent conductivity, has unique application value in the electronics, electrical, high-tech and jewelry industries. In recent years, with the growing demand for gold in high-tech industries, the price of gold has also risen rapidly. However, the reserves of high-grade gold resources in nature are limited, and the mining cost is also increasing with the consumption of resources. Faced with the challenges of limited gold resources and increasing demand for industrial gold, effective measures must be taken to recycle gold. At present, electronic waste and some industrial wastewater contain rich secondary gold resources. Recycling and reusing these resources can significantly make up for the consumption of gold resources in nature. Therefore, the secondary recovery and utilization of gold resources is of great significance to the sustainable development strategy.

[0003] Traditional gold recovery technology has the problems of low adsorbent efficiency and poor selectivity. Therefore, there is an urgent need for a potential material that can be used to adsorb and recover gold in wastewater. Summary of the invention

[0004] Features and advantages of the invention are set forth in part in the following description, or may be obvious from the description, or may be learned through practice of the invention.

[0005] In order to overcome the problems of the prior art, the present invention provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PVA / PEI composite nanofibers: polyvinyl alcohol powder and water were stirred in an oil bath at 85°C with a magnetic stirrer for 4 h to obtain a uniform and transparent spinning solution, namely solution A; polyethyleneimine and water were stirred at room temperature for 4 h to obtain another uniform and transparent spinning solution, namely solution B; solution A and solution B were mixed to obtain solution C, and solution C was spun in an electrospinning machine to obtain PVA / PEI composite nanofibers; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers obtained in S1 were cut into small pieces of 1*1 cm, the cut PVA / PEI composite nanofibers were mixed with glutaraldehyde, anhydrous ethanol was added, and cross-linked for 8 h under magnetic stirring at 85°C. After the reaction, the fibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers. S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers obtained in S2 were cut into small pieces of 1*1 cm, the cut GA-PVA / PEI nanofibers were mixed with n-propyl chloride, anhydrous ethanol was added, and the mixture was reacted for 12 h under magnetic stirring at room temperature; after the reaction, the mixture was washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain the modified GA-PVA / PEI-Cl nanofibers, i.e., quaternized GA-PVA / PEI-Cl nanofibers were obtained.

[0006] Preferably, in step S1, the mass ratio of the polyvinyl alcohol powder to the polyethyleneimine is 2-6:1.

[0007] Preferably, the mass percentage of the solute in the A solution and the B solution is 10%-20%.

[0008] Preferably, the mixing mass ratio of the PVA / PEI composite nanofibers to the glutaraldehyde is 1:2.

[0009] Preferably, the mixing mass ratio of the GA-PVA / PEI nanofibers to the n-propyl chloride is 1:10.

[0010] Preferably, in step S1, the parameters of the electrospinning machine are set as follows: voltage is 15.0-18.0 KV, spinning solution flow rate is 11.62 uL / min, drum speed is 300 r / min, receiving distance is 12-15 cm, spinning temperature and humidity are 25 ± 1 °C and 60 ± 5%, respectively.

[0011] Preferably, the present invention further provides a quaternary ammonium modified GA-PVA / PEI-Cl nanofiber, which is prepared by the preparation method of the quaternary ammonium modified GA-PVA / PEI-Cl nanofiber provided above.

[0012] Preferably, the present invention also provides an application of quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, wherein the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers are applied to AuCl4 - Selective recovery.

[0013] Compared with the prior art, the advantages and positive effects of the present invention are: 1. The quaternized GA-PVA / PEI-Cl nanofibers obtained by the present invention are obtained by quaternization modification. The surface of the obtained nanofibers is rich in positive charge, which can realize the reaction of AuCl4 in aqueous solution with negative charge. -- Selective enrichment adsorption.

[0014] 2. The quaternized GA-PVA / PEI-Cl nanofibers obtained by the present invention react with AuCl4 - The adsorption process involves multiple reaction mechanisms such as electrostatic effect, coordination effect and redox reaction, and therefore, it has a higher adsorption capacity and better adsorption effect.

[0015] 3. The quaternized GA-PVA / PEI-Cl nanofibers of the present invention exhibit superhydrophilicity, which can reduce the contact energy barrier between them and gold in the solution, and can effectively solve the problem of gold adsorption, recovery and removal in high concentration solutions, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present invention will be described in detail below with reference to the accompanying drawings and in combination with examples, and the advantages and implementation methods of the present invention will become more obvious. The contents shown in the accompanying drawings are only used to explain the present invention and do not constitute any limitation to the present invention in any sense. In the accompanying drawings: Figure 1 This is a schematic diagram of the process of quaternary ammonium modification of GA-PVA / PEI-Cl nanofibers in a specific embodiment of the present invention; Figure 2 Schematic diagram of the preparation of quaternary ammonium modified GA-PVA / PEI-Cl nanofibers in a specific embodiment of the present invention; Figure 3 Figures are scanning electron microscope images of nanofibers at various stages obtained in specific embodiment 3 of the present invention, wherein Figure a is a scanning electron microscope image of PVA / PEI composite nanofibers; Figure b is a scanning electron microscope image of GA-PVA / PEI nanofibers; Figure c is a scanning electron microscope image of quaternized GA-PVA / PEI nanofibers; Figure d is a diameter distribution diagram of PVA / PEI composite nanofibers; Figure e is a diameter distribution diagram of GA-PVA / PEI nanofibers; and Figure f is a diameter distribution diagram of quaternized GA-PVA / PEI nanofibers. Figure 4 The water contact angle diagrams of the PVA / PEI composite nanofibers, the GA-PVA / PEI nanofibers cross-linked with glutaraldehyde, and the quaternized GA-PVA / PEI-Cl nanofibers in the specific embodiment 3 of the present invention; Figure 5 The following is an analysis of the effect of pH on the adsorption process in a specific embodiment of the present invention. - Figure a is the analysis diagram of the influence of pH on the adsorption amount; Figure b is the analysis diagram of the Zata potential influence of pH; Figure 6 In the specific embodiment of the present invention, different AuCl4 - Analysis of the effect of initial concentration on the adsorption process; Figure 7This is an analysis diagram of the influence of different time on the adsorption process in a specific embodiment of the present invention; Figure 8 The quaternary ammonium modified GA-PVA / PEI-Cl nanofibers in a complex mixed solution for AuCl4 - Selective impact analysis diagram; Fig. 9 This is an analysis diagram of the effect of temperature on the adsorption process in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0017] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0018] Example 1

[0019] like Figure 1 and Figure 2 As shown, this embodiment provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically includes the following steps: S1. Preparation of PVA / PEI composite nanofibers: 2.0 g of polyvinyl alcohol (PVA) powder and 18 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=10%), which was recorded as solution A; 1.0 g of polyethyleneimine (PEI) and 4.0 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=20%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.310 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.620 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: Cut the GA-PVA / PEI nanofibers prepared in step S2 into small pieces of 1*1 cm, then weigh 0.20 g of the GA-PVA / PEI nanofiber small pieces, and place them and 2.0 g of n-propyl chloride in a round-bottom flask, then add 100 mL of anhydrous ethanol as solvent, and react for 12 hours under magnetic stirring at room temperature. After the reaction, the nanofibers are washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 hours to obtain quaternized GA-PVA / PEI-Cl nanofibers.

[0020] The obtained quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were used as adsorption materials for the recovery of gold in wastewater.

[0021] Polyethyleneimine (PEI) has good electrospinning performance due to the abundant primary amine, secondary amine and tertiary amine groups on its macromolecular chain. However, due to the strong polarity and intermolecular forces of PEI, its electrospinning process is not easy. Therefore, PEI is usually mixed with other polymers to improve its electrospinning performance. Polyvinyl alcohol (PVA) is a water-soluble polymer with many active hydroxyl groups. It has the characteristics of low cost, non-toxicity, good biocompatibility, good mechanical strength, and good electrospinnability. PVA / PEI composite nanofibers prepared by electrospinning can retain the excellent properties of both, are rich in amino groups, and are AuCl4 - active adsorption sites.

[0022] Electrospinning technology can be used to prepare nanofibers with a high specific surface area. The surface of the nanofibers is cross-linked and modified by surface modification technology to provide more nitrogen active sites, and then the surface is modified by quaternization to carry a large amount of positive charge. In addition, since the matrix materials PVA and PEI have a large number of hydrophilic groups and exhibit good hydrophilicity, the energy barrier for the adsorbent to contact gold in the solution can be reduced, significantly improving the adsorption effect of gold in the solution.

[0023] The technical solution adopted in this embodiment is: polyvinyl alcohol (PVA) and polyethyleneimine (PEI) are used as matrix materials, and electrospinning technology is used to prepare composite nanofibers. GA-PVA / PEI-Cl nanofibers are prepared by cross-linking modification using glutaraldehyde (GA) and using n-propyl chloride as the functional group for quaternary modification. The prepared quaternary modified GA-PVA / PEI-Cl nanofibers are reacted with AuCl4 - Through electrostatic interaction, coordination and redox interaction, AuCl4 -In addition, the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers prepared by the present invention have excellent hydrophilicity, reduce the energy barrier in the adsorption process, and can significantly improve the adsorption rate and adsorption capacity.

[0024] Example 2

[0025] This embodiment provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PVA / PEI composite nanofibers: 3.0 g of polyvinyl alcohol (PVA) powder and 17 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=15%), which was recorded as solution A; 0.5 g of polyethyleneimine (PEI) and 4.5 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=10%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.356 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.712 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers prepared in step S2 were cut into small pieces of 1*1 cm, and then 0.357 g of the GA-PVA / PEI nanofiber small pieces were weighed and placed in a round-bottom flask with 3.57 g of n-propyl chloride, and then 100 mL of anhydrous ethanol was added as solvent. The mixture was reacted for 12 h under magnetic stirring at room temperature. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain quaternized GA-PVA / PEI-Cl nanofibers.

[0026] The obtained quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were used as adsorption materials for the recovery of gold in wastewater.

[0027] Example 3

[0028] This embodiment provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PVA / PEI composite nanofibers: 3.5 g of polyvinyl alcohol (PVA) powder and 16.5 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=18%), which was recorded as solution A; 1 g of polyethyleneimine (PEI) and 4 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=20%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.368 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.736 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers prepared in step S2 were cut into small pieces of 1*1 cm, and then 0.369 g of the GA-PVA / PEI nanofiber small pieces were weighed and placed in a round-bottom flask with 3.69 g of n-propyl chloride, and then 100 mL of anhydrous ethanol was added as solvent. The mixture was reacted for 12 h under magnetic stirring at room temperature. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain quaternized GA-PVA / PEI-Cl nanofibers.

[0029] The obtained quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were used as adsorption materials for the recovery of gold in wastewater.

[0030] Example 4

[0031] This embodiment provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PVA / PEI composite nanofibers: 3.5 g of polyvinyl alcohol (PVA) powder and 16.5 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=18%), which was recorded as solution A; 0.875 g of polyethyleneimine (PEI) and 4.125 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=18%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.381 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.762 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers prepared in step S2 were cut into small pieces of 1*1 cm, and then 0.315 g of the GA-PVA / PEI nanofiber small pieces were weighed and placed in a round-bottom flask with 3.15 g of n-propyl chloride, and then 100 mL of anhydrous ethanol was added as solvent. The mixture was reacted for 12 h under magnetic stirring at room temperature. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain quaternized GA-PVA / PEI-Cl nanofibers.

[0032] The obtained quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were used as adsorption materials for the recovery of gold in wastewater.

[0033] Example 5

[0034] This embodiment provides a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PVA / PEI composite nanofibers: 4.0 g of polyvinyl alcohol (PVA) powder and 16 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=20%), which was recorded as solution A; 0.7 g of polyethyleneimine (PEI) and 4.3 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=14%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.410 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.820 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers prepared in step S2 were cut into small pieces of 1*1 cm, and then 0.290 g of the GA-PVA / PEI nanofiber small pieces were weighed and placed in a round-bottom flask with 2.9 g of n-propyl chloride, and then 100 mL of anhydrous ethanol was added as solvent. The mixture was reacted for 12 h under magnetic stirring at room temperature. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain modified GA-PVA / PEI-Cl nanofibers.

[0035] The obtained quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were used as adsorption materials for the recovery of gold in wastewater.

[0036] Sample characterization of this example: like Figure 3As shown in the figure, the surface morphology of the original PVA / PEI composite nanofibers, cross-linked GA-PVA / PEI nanofibers and quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were observed by scanning electron microscopy. It can be clearly observed that the original PVA / PEI composite nanofibers have uniform diameters and no beading phenomenon, showing a network structure with a diameter mainly distributed around 350 nm. Due to the cross-linking effect, the surface of the GA-PVA / PEI nanofibers after glutaraldehyde cross-linking is obviously rougher than that of the original PVA / PEI composite fibers, and the diameter is slightly increased to 370 nm. This change may be due to the cross-linking of the functional groups in PVA and PEI with glutaraldehyde, which increases the mass of the nanofibers. Due to grafting and modification, the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers become thicker after modification compared to the original PVA / PEI composite fibers. On the other hand, as Figure 4 As shown in the figure, the quaternary ammonium modified GA-PVA / PEI-Cl fibers have super hydrophilicity due to the introduction of a large number of hydrophilic groups. In short, the changes in the morphology of the modified fibers show that the quaternary ammonium modification on the surface of the nanofibers is successful and has super hydrophilicity.

[0037] Considering the influence of different factors on the adsorption results, static adsorption was used to investigate the adsorption of AuCl4 by quaternary ammonium modified GA-PVA / PEI-Cl nanofibers under different conditions. - The adsorption capacity of AuCl4 - The initial concentration of the solution (100-600 mg / L), adsorption temperature (25-45°C) and contact time (1-720 min) were determined. The entire adsorption process was carried out in a constant temperature oscillator. The AuCl4 - The concentration was determined by ICP-OES. The theoretical adsorption capacity was calculated according to the following formula: ; Where: Qe (mg / g) is the adsorption capacity; C0 (mg / L) is the initial concentration of the solution; C e (mg / L) is the equilibrium concentration of the solution; V (mL) is the volume of the solution; W (g) is the mass of the adsorbent.

[0038] like Figure 5 As shown in Figure 2, the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers showed good catalytic activity against AuCl4 in a wide pH range (2-3). -It has a good adsorption effect, and has the best adsorption capacity at pH=3. At pH=4, the adsorption capacity drops sharply, and after the pH is greater than 4, the adsorption capacity begins to gradually decrease. The reason for this phenomenon can be explained by the Zeta potential in the figure. It is mainly because when the pH is less than 8.7, the surface of the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers of the adsorption material has a positive charge, which is easy to react with the negatively charged AuCl4 - The adsorption behavior occurs between them through electrostatic attraction.

[0039] In order to study the effect of initial concentration on the adsorption capacity of quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, AuCl4 with concentrations of 100-600 mg / L was prepared. - The experiment was carried out at 25°C and the pH value of the solution was 3. Figure 6 It can be seen that as the concentration increases, the adsorption capacity is positively correlated with the initial concentration, and both - When the initial concentration reached 600 mg / L, the adsorption basically reached saturation.

[0040] The effect of contact time on the adsorption process is as follows Figure 7 As shown in the figure, the adsorption capacity increased relatively rapidly during the initial contact time of 400 min, which may be due to the fact that the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers had a large number of adsorption sites at this time. After that, the adsorption rate climbed relatively slowly, and the adsorption basically reached equilibrium at 360 min. This result may be related to the fact that the adsorption sites of the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were largely occupied. On the other hand, a large amount of AuCl4 - Adsorption leads to a decrease in the ion concentration in the solution, thereby weakening the driving force for mass transfer.

[0041] Selectivity experimental verification: 10 mg of quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were added to 20 mL of a mixed solution containing Fe(III), Co(II), Ni(II), Cd(II), Pb(II) and Au(III) at a concentration of 200 mg / L for adsorption. The results are shown in Figure 2. Figure 8 As shown in the figure, the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers have a significant effect on the AuCl4 - It showed high adsorption capacity, but almost no adsorption for other ions. This showed that the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers were - The modified GA-PVA / PEI-Cl nanofibers have excellent selectivity for AuCl4 -The selectivity of the ion is attributed to its surface rich in positive charges, which easily react with AuCl4 in the form of negative ions. - Static electricity is generated between them.

[0042] In addition, it should be noted that, based on the same principle, the selective adsorption effect of the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers provided by the present invention is not limited to AuCl4 in a mixed solution of Fe(III), Co(II), Ni(II), Cd(II), Pb(II) and Au(III). - Specific recognition.

[0043] The effect of temperature on the adsorption process was investigated by thermodynamic experiments at different temperatures of 25°C-45°C (contact time 360 ​​min, pH=3). The results are as follows: Fig. 9 As shown. It can be concluded that within a certain temperature range, as the temperature gradually rises, the adsorption material for AuCl4 - The adsorption capacity of AuCl4 - This result may be due to the fact that AuCl4 - The rate of diffusion is accelerated.

[0044] From the above experiments, it can be seen that the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers have a strong - It has specific recognition and can quickly and specifically identify and adsorb AuCl4 in wastewater mixed with other metal ions. - , and thus the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers can be used to recover gold in wastewater.

[0045] Example 6

[0046] This embodiment provides a method for preparing GA-PVA / PEI nanofibers that have not been quaternized, which specifically includes the following steps: S1. Preparation of PVA / PEI composite nanofibers: 2.0 g of polyvinyl alcohol (PVA) powder and 18 g of water were added to a round-bottom flask, and stirred with a magnetic stirrer in an oil bath at 85°C for 4 h to obtain a uniform and transparent spinning solution (wt=10%), which was recorded as solution A; 1.0 g of polyethyleneimine (PEI) and 4.0 g of water were added to a beaker, and stirred at room temperature for 4 h to obtain a uniform and transparent spinning solution (wt=20%), which was recorded as solution B. Solution A and solution B were mixed evenly to obtain solution C, and then the obtained solution C was placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 11.62 uL / min, roller speed of 300 r / min, receiving distance of 15 cm, spinning temperature and humidity of 24°C and 55%, respectively; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers prepared in step S1 were cut into small pieces of 1*1 cm, and then 0.310 g of the PVA / PEI composite nanofiber small pieces were weighed and placed in a round-bottom flask with 0.62 g of glutaraldehyde (GA), and then 100 mL of anhydrous ethanol was added as a solvent. The cross-linking reaction was carried out at 85°C under magnetic stirring for 8 h. After the reaction, the nanofibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers; The obtained GA-PVA / PEI nanofibers without quaternary ammonium modification were used as adsorption materials for the recovery of gold in wastewater.

[0047] The nanofibers obtained in Examples 1-6 were used to recover gold from wastewater.

[0048] Adsorption test: 10 mg of each of the quaternized GA-PVA / PEI-Cl nanofibers prepared in Examples 1-5 and the GA-PVA / PEI nanofibers in Example 6 were taken, and a certain volume of wastewater solution was taken from the wastewater pool at the same time. The pH value of the wastewater solution was adjusted to pH=3 using hydrochloric acid, and then 6 portions of the wastewater solution with the same volume of 25 mL were measured from the acid-adjusted wastewater solution. The weighed quaternized GA-PVA / PEI-Cl nanofibers and the GA-PVA / PEI nanofibers cross-linked with glutaraldehyde were placed in the 6 portions of wastewater solution, respectively. The temperature was controlled at 25°C and the solution was taken out after constant temperature oscillation for 15 h. The concentrations of each metal ion in the solution before and after adsorption were determined by inductively coupled plasma emission spectrometry (ICP-OES). The initial concentrations of each ion in the wastewater solution before adsorption were: Au(III) was 166.1 mg / L, Co(II) was 172.1 mg / L, Fe(III) was 159.9 mg / L, Ni(II) is 165.4 mg / L, Pb(II) is 209.5 mg / L, and the concentration of each metal ion in the wastewater solution is measured after adsorption, and the adsorption capacity of each nanofiber for each metal in the wastewater is calculated. The above experiment is repeated three times and the average value is taken, that is, the nanofibers of Examples 1-5 and Example 6 are subjected to three repeated adsorption tests, and the adsorption capacity data are shown in Table 1: Table 1 Experimental parameters of Examples 1-6 and the adsorption capacity data of each nanofiber for Au(III) ;

[0049] As shown in Table 1, the quaternary ammonium modified GA-PVA / PEI-Cl nanofibers have a strong - The anion adsorption capacity is significantly increased, and the PVA and PEI molecules can be used as an adsorption material for the adsorption of gold in wastewater. At the same time, since PVA and PEI molecules contain a large number of hydrophilic groups, such as hydroxyl and amino groups, they can form hydrogen bonds with water molecules. The PVA / PEI composite nanofibers cross-linked with glutaraldehyde form a stable cross-linked network. This cross-linking increases the number of hydrophilic groups on the surface of the material. Although the PVA / PEI composite nanofibers can improve the hydrophilicity of the material, due to the lack of quaternary ammonium modification, the hydrophilicity of the cross-linked GA-PVA / PEI nanofibers is still relatively poor compared with the quaternary ammonium GA-PVA / PEI-Cl nanofibers. Therefore, when the material is used as an adsorption material for the recovery of gold in wastewater, the adsorption effect is poor.

[0050] The preferred embodiments of the present invention are described above with reference to the accompanying drawings. A person skilled in the art may implement the present invention in a variety of variations without departing from the scope and essence of the present invention. For example, a feature shown or described as part of one embodiment may be used in another embodiment to obtain another embodiment. The above are only preferred feasible embodiments of the present invention, and do not limit the scope of rights of the present invention. Any equivalent changes made using the contents of the present specification and the accompanying drawings are included in the scope of rights of the present invention.

Claims

1. A method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, characterized in that: The specific steps include: S1. Preparation of PVA / PEI composite nanofibers: polyvinyl alcohol powder and water were stirred in an oil bath at 85°C with a magnetic stirrer for 4 h to obtain a uniform and transparent spinning solution, namely solution A; polyethyleneimine and water were stirred at room temperature for 4 h to obtain another uniform and transparent spinning solution, namely solution B; solution A and solution B were mixed to obtain solution C, and solution C was spun in an electrospinning machine to obtain PVA / PEI composite nanofibers; S2. Preparation of GA-PVA / PEI nanofibers: The PVA / PEI composite nanofibers obtained in S1 were cut into small pieces of 1*1 cm, the cut PVA / PEI composite nanofibers were mixed with glutaraldehyde, anhydrous ethanol was added, and cross-linked for 8 h under magnetic stirring at 85°C. After the reaction, the fibers were washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain cross-linked GA-PVA / PEI nanofibers. S3. Preparation of quaternized GA-PVA / PEI-Cl nanofibers: The GA-PVA / PEI nanofibers obtained in S2 were cut into small pieces of 1*1 cm, the cut GA-PVA / PEI nanofibers were mixed with n-propyl chloride, anhydrous ethanol was added, and the mixture was reacted for 12 h under magnetic stirring at room temperature; after the reaction, the mixture was washed with deionized water for 3-4 times and then transferred to a vacuum freeze drying oven for freeze drying for 24 h to obtain the modified GA-PVA / PEI-Cl nanofibers, i.e., quaternized GA-PVA / PEI-Cl nanofibers were obtained.

2. The method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers according to claim 1, characterized in that: In step S1, the mass ratio of the polyvinyl alcohol powder to the polyethyleneimine is 2-6:

1.

3. The method for preparing a quaternary ammonium modified GA-PVA / PEI-Cl nanofiber according to claim 1, characterized in that: The mass percentage of the solute in the A solution and the B solution is 10%-20%.

4. The method for preparing a quaternary ammonium modified GA-PVA / PEI-Cl nanofiber according to claim 1, characterized in that: The mixing mass ratio of the PVA / PEI composite nanofibers to the glutaraldehyde is 1:

2.

5. The method for preparing a quaternary ammonium modified GA-PVA / PEI-Cl nanofiber according to claim 1, characterized in that: The mixing mass ratio of the GA-PVA / PEI nanofibers to the n-propyl chloride is 1:

10.

6. The method for preparing a quaternary ammonium modified GA-PVA / PEI-Cl nanofiber according to claim 1, characterized in that: In step S1, the parameters of the electrospinning machine are set as follows: voltage is 15.0-18.0 KV, spinning solution flow rate is 11.62uL / min, drum speed is 300 r / min, receiving distance is 12-15 cm, spinning temperature and humidity are 25 ± 1 °C and 60 ± 5%, respectively.

7. A quaternary ammonium modified GA-PVA / PEI-Cl nanofiber, characterized in that: The nanofiber is prepared by a method for preparing quaternary ammonium modified GA-PVA / PEI-Cl nanofibers as claimed in any one of claims 1 to 6.

8. An application of quaternary ammonium modified GA-PVA / PEI-Cl nanofibers, characterized in that: The quaternary ammonium modified GA-PVA / PEI-Cl nanofibers described in claim 7 are applied to AuCl4 - Selective recovery.

Citation Information

Patent Citations

  • Heavy metal ion adsorbed film and preparation

    CN101254457A

  • In-situ preparation method of functional gold nanoparticle / electrostatic spinning composite nano fibrofelt

    CN101886331A

  • Imprinted crosslinked chitosan nanofiber membrane containing heavy metal ions and preparation method thereof

    CN107159157A

  • Preparation method of functional chitosan, polyvinyl alcohol and polycaprolactam composite nanofibrous membrane

    CN107904782A

  • Polyethyleneimine-grafted nanocellulose shaped body, preparation thereof, andselective adsorbent using the same for platinum group metals

    KR102118413B1